2020
DOI: 10.1007/978-3-030-49183-3_24
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Human Behaviour in Flight Operation Using Eye-Tracking Technology

Abstract: A clear understanding of how the pilot processes the information in the cockpit while carrying out particular tasks is crucial for developing the Human-Machine Interface and inceptors that help reduce pilot workload. Eye-tracking data synchronised with aircraft dynamics data is used here to study the high-workload scenario of executing an offset landing in an engineering flight simulator. The study focused on identifying differences in behavioural patterns between line pilots and test pilots. Evidence for sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…When evaluating the relationship between humans and equipment through eye-tracking devices, eye movement data were used to analyse human behaviours. This hypothesis was confirmed by many previous researchers [14], such as mental fatigue [15], cognitive load [16], information acquisition [17], situational awareness [18], scanning behaviours [19], attention [20], physiological measurements [21], workload [22, 23], interface evaluation and human-computer interaction [24, 25]. Research on eye movement data that predicted pilots’ behaviour included how different role assignments influenced decisions in high-risk environments, and how to predict pilots’ decisions by paying attention to relevant information about pilots’ choices [26].…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…When evaluating the relationship between humans and equipment through eye-tracking devices, eye movement data were used to analyse human behaviours. This hypothesis was confirmed by many previous researchers [14], such as mental fatigue [15], cognitive load [16], information acquisition [17], situational awareness [18], scanning behaviours [19], attention [20], physiological measurements [21], workload [22, 23], interface evaluation and human-computer interaction [24, 25]. Research on eye movement data that predicted pilots’ behaviour included how different role assignments influenced decisions in high-risk environments, and how to predict pilots’ decisions by paying attention to relevant information about pilots’ choices [26].…”
Section: Introductionsupporting
confidence: 79%
“…scanning behaviours [19], attention [20], physiological measurements [21], workload [22,23], interface evaluation and human-computer interaction [24,25].Research on eye movement data that predicted pilots' behaviour included how different role assignments influenced decisions in high-risk environments, and how to predict pilots' decisions by paying attention to relevant information about pilots' choices [26]. When using eye movement to predict dangerous situations, Francisco [27] found that saccade, gaze, blink and gaze dispersion in horizontal and vertical dimensions in eye movement features were more likely to predict the occurrence of dangerous situations.…”
Section: Application Of Eye Movement Datamentioning
confidence: 99%
“…The study recorded eye movement data and analysed key indicators related to discernibility, perceptibility, and accessibility of HUD information and explored the optimal colour coding scheme for key elements of the HUD against different background brightness levels, with their findings providing insights for improving HUD design and optimising the cognitive performance of pilots in various flight environments, offering guidance for HUD enhancement and reference for future research in this area. Additionally, the analysis of the pilots' gaze distribution is used to measure how the pilots' task load influence visual behaviour and performance [20,21] and, generally, understanding of how the pilot processes the information in the cockpit while carrying out particular tasks [22]. A particular case is [23] as it examines pilot eye movements during approach phases, with results indicating similarities in eye behaviour between the pilot flying and the pilot monitoring.…”
Section: Use Of Eye Tracking In Aviationmentioning
confidence: 99%
“…The effect of this engagement is one-off and requires redefining the AOI both when changing the operator and the flight task being recorded. This functionality is important, especially in the case of complex Human-Machine Interfaces (HMI) systems, where it is indispensable to transfer large amounts of data in the shortest possible time, e.g., production line operators or operators of ground air traffic control stations of unmanned systems [7][8][9][10][11]. The approach proposed in this paper is based on well-known and used eye-tracking systems which, due to their universality and targeting a different audience, do not allow for application in the areas and tasks that are the purpose of this paper.…”
Section: Introductionmentioning
confidence: 99%